2020
DOI: 10.33714/masteb.675929
|View full text |Cite
|
Sign up to set email alerts
|

Diet Composition of Bluefish Pomatomus saltatrix (Linnaeus, 1766) in the Sea of Marmara

Abstract: In this study, diet composition of bluefish Pomatomus saltatrix (Linnaeus, 1766) was investigated. A total of 512 bluefish samples were monthly collected from commercial fishing boats operating in the Sea of Marmara between January and December 2014. It was determined that the total length distribution of the samples varied between 12.3-47.3 cm. 367 of them (71.67%) were found to be the full of the stomach. The nutritional composition of stomach contents only two main prey groups (teleostei and crustacean) wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…The global database collated here confirmed this tenet: the differences in TP values among locations was paralleled by a considerable variability observed for the same location when different baseline species were used (Table 2). Anchovies belonging to the genus Engraulis are a dominant item in the diet of bluefish worldwide (Juanes et al, 1996;Lucena et al, 2000;Schilling et al, 2017;Bal et al, 2020); therefore, we are confident regarding the robustness of estimations for the Strait of Otranto. For the Gulf of Taranto the demersal Lithognathus mormyrus was used as the baseline species.…”
Section: Table 2 Continuedmentioning
confidence: 71%
See 2 more Smart Citations
“…The global database collated here confirmed this tenet: the differences in TP values among locations was paralleled by a considerable variability observed for the same location when different baseline species were used (Table 2). Anchovies belonging to the genus Engraulis are a dominant item in the diet of bluefish worldwide (Juanes et al, 1996;Lucena et al, 2000;Schilling et al, 2017;Bal et al, 2020); therefore, we are confident regarding the robustness of estimations for the Strait of Otranto. For the Gulf of Taranto the demersal Lithognathus mormyrus was used as the baseline species.…”
Section: Table 2 Continuedmentioning
confidence: 71%
“…S2). For the Strait of Otranto, E. encrasicolus was chosen as it is a highly preferred prey for pelagic P. saltatrix populations (e.g., Georgieva & Daskalov, 2019;Bal et al, 2020); indeed, large schools of bluefish are frequently observed in the fall chasing forage fish shoals moving along the Adriatic coast of the Salento Peninsula (Mancini, personal observation).…”
Section: Study Sites and Sample Collectionmentioning
confidence: 99%
See 1 more Smart Citation